Endophytic and rhizospheric bacterial communities are affected differently by the host plant species and environmental contamination - da Silva Maciel, Jonatham Hercules; Mello, Ivani Souza; Vendrusculo, Suzana Junges; Senabio, Jaqueline Alves; da Silva, Rafael Correia [UNESP]; de Siqueira, Adriano Buzutti; Pinheiro, Daniel Guariz [UNESP]; Soares, Marcos Antonio (Springer Nature, 2021)
Bacteria are associated with the root system of plants in the endophytic and rhizospheric micro-habitats. In this paper, we used cultivation-independent methods to examine how the soil mercury contamination (present or absent) and the host plant species (Aeschynomene fluminensis and P. acuminatum) interfered with endophytic and rhizospheric bacterial communities in a humid area of the Pantanal biome. The capacity of the most abundant species to remediate the metal was assessed in cells immobilized on alginate spheres. The endophytic and rhizospheric communities were composed of respectively 22 and 26 phyla, 237 and 382 genera, and 644 and 3549 bacterial operational taxonomic units. The soil mercury contamination increased the alpha diversity indicators (p < 0.05, test T) only in the rhizospheric micro-habitat. The presence of the metal did not affect the beta diversity (composition and abundance) of endophytic bacteria (p < 0.05; ANOSIN), but differently influenced the interactions within endophytic and rhizospheric bacterial communities. The host species and the presence of the metal significantly altered the beta diversity of the rhizospheric communities (p < 0.05; ANOSIN). Arthrobacter defluvii_C11, Bacillus anthracis_C77, Pantoea_agglomerans_BacI11 and Acinetobacter_baumannii_BacI43 were immobilized on alginate beads, and removed more than 80% of the mercury in solution. Future studies are required to examine whether the endophytic environment acts as a buffer over other contaminants and reduces the impact of the metal on endophytic bacterial communities.
Keywords: Bioremediation; Diversity; Mercury; Pantanal; Trace metals